2022
DOI: 10.1002/alz.12529
|View full text |Cite
|
Sign up to set email alerts
|

Lower serum testosterone concentrations are associated with a higher incidence of dementia in men: The UK Biobank prospective cohort study

Abstract: Introduction The association of testosterone concentrations with dementia risk remains uncertain. We examined associations of serum testosterone and sex hormone–binding globulin (SHBG) with incidence of dementia and Alzheimer's disease. Methods Serum total testosterone and SHBG were measured by immunoassay. The incidence of dementia and Alzheimer's disease (AD) was recorded. Cox proportional hazards regression was adjusted for age and other variables. Results In 159,411 community‐dwelling men (median age 61, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 36 publications
1
21
2
Order By: Relevance
“…Conversely, in a smaller study involving 296 older men by Schneider et al, testosterone has been shown to increase the risk of panic and phobic anxiety in patients with a genetically determined long CAG repeat polymorphism of the androgen receptor [ 137 ]. Regarding the effects of androgens in the elderly, it has been reported that low testosterone serum levels are independently associated with incident dementia and Alzheimer’s disease, confirmed by an increased incidence of those conditions in ADT patients [ 147 , 148 ]. Conversely, further evidence is required to enlighten the relation between testosterone and Parkinson’s disease, considering the neuroprotective effects of 5-alfa reductase inhibitors in animal models [ 149 ].…”
Section: Clinical Findingsmentioning
confidence: 99%
“…Conversely, in a smaller study involving 296 older men by Schneider et al, testosterone has been shown to increase the risk of panic and phobic anxiety in patients with a genetically determined long CAG repeat polymorphism of the androgen receptor [ 137 ]. Regarding the effects of androgens in the elderly, it has been reported that low testosterone serum levels are independently associated with incident dementia and Alzheimer’s disease, confirmed by an increased incidence of those conditions in ADT patients [ 147 , 148 ]. Conversely, further evidence is required to enlighten the relation between testosterone and Parkinson’s disease, considering the neuroprotective effects of 5-alfa reductase inhibitors in animal models [ 149 ].…”
Section: Clinical Findingsmentioning
confidence: 99%
“…UK Biobank also utilised registry data to ascertain diagnoses of dementia and dementia due to Alzheimer disease, using an algorithm validated against clinical expert adjudication of full-text medical records [ 64 , 65 ]. Thus, two large population-based cohort studies, of middle-aged to older men in UK Biobank, and older men in HIMS, found consistent associations of lower baseline testosterone concentrations with higher incidence of dementia, and of dementia due to Alzheimer disease [ 13 , 14 ]. Higher SHBG may be associated with both cognitive decline in older men [ 61 ], and higher incidence of dementia and Alzheimer’s disease in middle-aged to older men [ 13 ].…”
Section: Observational Studies Of Testosterone Cognitive Decline and ...mentioning
confidence: 99%
“…Lower baseline testosterone was associated with higher risk of incident dementia (hazard ratio 1.14 per 1 SD decrease), as was lower cFT (hazard ratio 1.18 per 1 SD decrease). Lower estradiol was associated with higher risk of incident dementia (hazard ratio 1.11 per 1 SD decrease) but SHBG was not associated Marriott et al [ 13 ] 159,411 40–69 7 826 men developed dementia, of which 288 were classified as having Alzheimer’s disease b . Lower testosterone concentrations were associated with higher incidence of dementia (overall trend P = 0.001, hazard ratio 1.43 for lowest vs highest quintile), and Alzheimer’s disease (overall trend P = 0.017, hazard ratio 1.80 for lowest vs highest quintile).…”
Section: Observational Studies Of Testosterone Cognitive Decline and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, androgens such as testosterone are regulated by the HPG axis. As the physiological level of testosterone decreases with aging in AD, androgen can prevent Aβ plaque formation and reduce Tau phosphorylation ( 75 ). The protective effect of testosterone has been proved to be related to the glycogen synthase pathway ( 76 ).…”
Section: Manuscript Formattingmentioning
confidence: 99%